1992
DOI: 10.1038/ki.1992.57
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of renal involvement in familial Mediterranean fever

Abstract: Kidney biopsies were performed on fifteen patients with a long-standing history of familial Mediterranean fever (FMF) and evidence of renal involvement. On light microscopy, seven patients were found to have amyloidosis, six mesangial proliferative glomerulonephritis (MsPGN) and two patients rapid progressive glomerulonephritis (RPGN). Immunofluorescent studies of the six biopsies with MsPGN were positive for mesangial IgA deposits (IgA nephropathy) in three patients and IgM mesangial deposits in three (IgM ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 21 publications
3
36
0
1
Order By: Relevance
“…They found that among 25 FMF patients, 10 (40%) had NAKD including mainly focal glomerulonephritis and focal segmental glomerular sclerosis. This rate of NAKD is similar to that reported by Said, et al 6 . Contrary to these results, among 2436 patients from the Turkish FMF study group, 12.9% had biopsy-proven amyloidosis (amyloid kidney disease, AKD), while only 0.8% had NAKD 15 .…”
Section: Rheumatologysupporting
confidence: 80%
See 2 more Smart Citations
“…They found that among 25 FMF patients, 10 (40%) had NAKD including mainly focal glomerulonephritis and focal segmental glomerular sclerosis. This rate of NAKD is similar to that reported by Said, et al 6 . Contrary to these results, among 2436 patients from the Turkish FMF study group, 12.9% had biopsy-proven amyloidosis (amyloid kidney disease, AKD), while only 0.8% had NAKD 15 .…”
Section: Rheumatologysupporting
confidence: 80%
“…In the report by Said, et al 6 , and in an article by Kukuy, et al in this issue of The Journal 10 , no cases of HSP or PAN were noted, probably because renal biopsy is usually not indicated in patients with HSP and because PAN is rare 6,10 . In these series, types of NAKD were similar to those expected in non-FMF patients, where IgA nephropathy, focal segmental glomerulosclerosis, and mesangial lesions are commonly seen.…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Blood analysis revealed a creatinine level of 0.81 mg/dL, urinalysis revealed proteinuria (+), hematuria, and a 24 hour urinary protein collection of 960 mg/day. Serological tests for glomerulonephritis, mesangial IgA nephropathy, IgM nephropathy, diffuse proliferative glomerulonephritis) have also been reported in patients with FMF [7][8][9] . We hereby present nine FMF patients with biopsy proven glomerulonephritis, who have been followed by the Nephrology Department of Cumhuriyet University.…”
Section: Casementioning
confidence: 99%
“…Said et al reported two patients diagnosed with FMF and IgA nephritis treated with colchicine who were not taking drugs regularly before the GN diagnosis. They had significant improvement at 3-6 months after regular treatment (26). In a recent study, Gok et al described a patient with FMF who presented with gross hematuria and protracted febrile myalgia.…”
Section: Dıscussıonmentioning
confidence: 99%